The story of my life : an Afghan girl on the other side of the sky - Ahmedi, Farah (Simon Spotlight Entertainment, 2005)
Farah Ahmedi, the victim of a land mine when she was just twelve years old, tells about her childhood in Afghanistan, a country trapped in war her entire life, and discusses the challenges she has faced as a result of losing her leg, and in trying to adapt to living in the United States.